2015
DOI: 10.1055/s-0035-1558100
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Vietnamese Medicinal Plant Extracts with Recombinantly Expressed Human Neurokinin-1 Receptor

Abstract: !A primary functional receptor screening assay was performed to examine the effects of methanolic extracts from ten Vietnamese medicinal plants on the human neurokinin-1 receptor expressed from Semliki Forest virus vectors in Chinese hamster ovary cells. Extracts from Piper nigrum, Stephania cambodica and Styphnolobium japonicum were found to exert inhibition on agonist-induced human neurokinin-1 receptor activity. Secondary assays and high performance liquid chromatography of the lead compounds addressed a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…For instance, it was demonstrated that samples from Ligularia fischeri leaves collected in summer (June) showed higher phenolic compounds, stronger anti-oxidative, and anti-microbial activity than samples collected in winter (December) [ 64 ]. Moreover, the location plays an important role as demonstrated for the differences in potency of NK1 receptor inhibition for Vietnamese plants collected from different parts of the country [ 26 ]. Furthermore, fruit from high-bush blueberries ( Vaccinium corymbosum ) and low-bush blueberries ( Vaccinium angustifolium ) showed differences in the contents of anthocyanins and total phenolic compounds [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was demonstrated that samples from Ligularia fischeri leaves collected in summer (June) showed higher phenolic compounds, stronger anti-oxidative, and anti-microbial activity than samples collected in winter (December) [ 64 ]. Moreover, the location plays an important role as demonstrated for the differences in potency of NK1 receptor inhibition for Vietnamese plants collected from different parts of the country [ 26 ]. Furthermore, fruit from high-bush blueberries ( Vaccinium corymbosum ) and low-bush blueberries ( Vaccinium angustifolium ) showed differences in the contents of anthocyanins and total phenolic compounds [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively potent binding inhibition was observed for extracts from E. indica and P. vulgaris , whereas the other plant extracts showed only weak or no inhibition. More recently, functional screening of 10 Vietnamese medicinal plants on SFV-based expression of the NK1 receptor in CHO cells demonstrated agonist-induced activity for extracts from Piper nigrum , Stephania cambodica , and Styphnolobium japonicum [ 26 ].…”
Section: Effect Of Plant Extracts On Cns Receptors and Therapeuticmentioning
confidence: 99%
“…In Vietnam, the tuber of S. cambodica is used in combination with other plants for treatment of various diseases such as depression, asthma, hypertension… (Do et al 1999). Despite its well-established use, few phytochemical studies have been undertaken on S.cambodica (Thanh and Hung 2011;Dinh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rotundine (l-tetrahydropalmatine) the main alkaloid isolated from S. cambodica tuber has been shown to be responsible for the inhibition of neurokinine-1 receptor gene expression (Dinh et al 2015). The presence of rotundine in S. cambodica tuber could justify its traditional use as an anxiolytic remedy in Cambodia since in Vietnam and China, rotundine is used as an anxiolytic and hypnotic drug (Wang and Mantsch 2014).…”
Section: Introductionmentioning
confidence: 99%